SPECT-CT Assessment of Pseudarthrosis after Spinal Fusion: Diagnostic Pitfall due to a Broken Screw - Olivier Rager; Gaël Amzalag; Arthur Varoquaux; Karl Schaller; Osman Ratib; Enrico Tessitore (Case Reports in Orthopedics)
A 43-year-old drug addicted female was referred for a L5-S1 posterolateral in situ fixation with autologous graft because of an L5/S1 severe discopathy with listhesis. After six months, low back pain recurred. A Tc-99m HDP SPECT-CT diagnosed a pseudarthrosis with intense uptake of the L5-S1 endplates and a fracture of the right S1 screw just outside the metal-bone interface without any uptake or bone resorption around the screw. The absence of uptake around a broken screw is a pitfall that the physician should be aware of.